Human rights and surrogate motherhood in the frame of new forms of family - Aguilar Grieder, Hilda (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
This study analyses one actual institution who has opened a deep debate in Spain and in other countries: the surrogate motherhood. The treatment of this problem can be done in different perspectives. In this study we only pretend to analyse the human rights involved in the surrogate motherhood, because the treatment of the different problems of this institution depends on this principal matter.